2017
DOI: 10.3390/ijms18051065
|View full text |Cite
|
Sign up to set email alerts
|

First Report of a Fatal Case Associated with EV-D68 Infection in Hong Kong and Emergence of an Interclade Recombinant in China Revealed by Genome Analysis

Abstract: A fatal case associated with enterovirus D68 (EV-D68) infection affecting a 10-year-old boy was reported in Hong Kong in 2014. To examine if a new strain has emerged in Hong Kong, we sequenced the partial genome of the EV-D68 strain identified from the fatal case and the complete VP1, and partial 5′UTR and 2C sequences of nine additional EV-D68 strains isolated from patients in Hong Kong. Sequence analysis indicated that a cluster of strains including the previously recognized A2 strains should belong to a sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 54 publications
2
28
1
Order By: Relevance
“…Here we report on the differential infectivity between various contemporary and historical EV-D68 strains in SH-SY5Y as measured by viral replication, cell viability, CPE, and immunofluorescence. The clade specificity of neuropathogenesis previously reported ( 10 , 22 , 26 28 , 33 , 34 ) between contemporary and historical strains is observed in the neurotropism in SH-SY5Y cells ( Fig. 5 ).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Here we report on the differential infectivity between various contemporary and historical EV-D68 strains in SH-SY5Y as measured by viral replication, cell viability, CPE, and immunofluorescence. The clade specificity of neuropathogenesis previously reported ( 10 , 22 , 26 28 , 33 , 34 ) between contemporary and historical strains is observed in the neurotropism in SH-SY5Y cells ( Fig. 5 ).…”
Section: Discussionsupporting
confidence: 61%
“…EV-D68 has continued to evolve since the 2014 outbreak, which is unsurprising as mutation and recombination are known to occur in enteroviruses ( 23 25 ). Sequence analysis has led to the classification of a new clade, D (a subclade of A) ( 26 , 27 ), and a new subclade, B3, has emerged and quickly expanded ( 26 , 28 , 29 ). Neurological symptoms have been associated with the novel B3 clade in Sweden ( 30 ), The Netherlands ( 31 ), Taiwan ( 32 ), Italy ( 33 ), and the United States ( 34 ), which experienced another AFM outbreak during the 2016 enterovirus season (summer and fall), with a total of 149 confirmed cases ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The extended primer grip of the poliovirus polymerase highlighted by the work presented herein is conserved across picornavirus species groups and likely mediates genetic exchange between viruses in nature. Intraspecies recombination is well documented for enterovirus species A (39, 67), species B (38, 68), species C (36) and species D viruses (69, 70), as well as rhinovirus species groups (37, 71), parechoviruses (35) and non-human enteroviruses (41). cVDPVs arise, in part, due to improved fitness from genetic exchange with non-polio group C enteroviruses in the field (4650).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, enterovirus-D68 has emerged in recent years in various countries and is increasingly recognized as an important respiratory pathogen in the young and immunocompromised. In the article by Yip et al, the first fatal case of EV-D68 infection and genetic diversity of EV-D68 strains in Hong Kong were described [ 14 ]. The study also found a newly emerged subclade B3 and an interclade recombination between clade A and D2 strains in China.…”
Section: Editorialmentioning
confidence: 99%